2017
DOI: 10.1016/j.jmb.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization and Molecular Interactions of the Schizosaccharomyces pombe Ccq1–Tpz1–Poz1 Shelterin Complex

Abstract: The shelterin complex is a macromolecular assembly of proteins that binds to and protects telomeric DNA, which composes the ends of all linear chromosomes. Shelterin proteins prevent chromosome ends from fusing together and from eliciting erroneous induction of DNA damage response pathways. Additionally, shelterin proteins play key roles in regulating the recruitment and activation of telomerase, an enzyme that extends telomeric DNA. In fission yeast, Schizosaccharomyces pombe, interactions between the shelter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Gel-filtration analysis showed that Poz1, Ccq1, Tpz1, and Pot1 form a stable quaternary complex (Supplementary information, Figure S9). A recent study reported that, in addition to Poz1, Ccq1 can also form a homodimer [47]. Our yeast two-hybrid analysis confirmed that the C-terminal coiled-coil domain of Ccq1 (residues 439-735) indeed mediates homodimerization interaction (Supplementary information, Figure S10).…”
Section: Functional Analyses Of the Poz1-rap1 Interaction And Poz1 DIsupporting
confidence: 82%
“…Gel-filtration analysis showed that Poz1, Ccq1, Tpz1, and Pot1 form a stable quaternary complex (Supplementary information, Figure S9). A recent study reported that, in addition to Poz1, Ccq1 can also form a homodimer [47]. Our yeast two-hybrid analysis confirmed that the C-terminal coiled-coil domain of Ccq1 (residues 439-735) indeed mediates homodimerization interaction (Supplementary information, Figure S10).…”
Section: Functional Analyses Of the Poz1-rap1 Interaction And Poz1 DIsupporting
confidence: 82%
“…For instance, cross-linking has been successfully coupled with phylogenetic sequence alignment to identify potential evolutionarily-conserved, functionally important residues. Subsequent mutation studies of candidate sites confirmed loss-of-function mutants, permitting localization of protein interaction interfaces in Schizosaccharomyces pombe telomere complexes 97,100 . Similarly, cross-linking data was used to direct truncation/deletion mutagenesis for identification of protein binding domains involved in exocytosis and microtubule complexes 140 .…”
Section: Xl-ms Strategies For Structural Analysis Of Protein Complmentioning
confidence: 91%
“…Both types of acquisition methods provide comparable and complementary results during data-dependent analyses. This MS n -based workflow has been successfully applied to map protein-protein interactions and elucidate architectures of protein complexes in vitro and in vivo 74,79,95100 .…”
Section: Strategies To Overcome Inherent Challenges In Xl-ms Studiesmentioning
confidence: 99%
“…Stat3 is also reportedly required for arthritis development in RA 37 39 . By contrast, inflammasome activation followed by expression of inflammatory cytokines by macrophages 40 reportedly promotes pathogenesis of auto-inflammatory syndromes 41 43 . However, inflammasome-independent auto-inflammatory syndromes have also been reported 44 , 45 ; thus not all mechanisms underlying auto-inflammatory syndromes have been defined 46 .…”
Section: Discussionmentioning
confidence: 99%